2012
DOI: 10.1155/2012/569520
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Response to Chronic Intermittent Hypoxia with a Transition from Adaptation to Maladaptation:The Role of Hydrogen Peroxide

Abstract: Obstructive sleep apnea (OSA) is a highly prevalent respiratory disorder of sleep, and associated with chronic intermittent hypoxia (CIH). Experimental evidence indicates that CIH is a unique physiological state with potentially “adaptive” and “maladaptive” consequences for cardio-respiratory homeostasis. CIH is also a critical element accounting for most of cardiovascular complications of OSA. Cardiac response to CIH is time-dependent, showing a transition from cardiac compensative (such as hypertrophy) to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 118 publications
2
30
0
Order By: Relevance
“…Exposure to IHH increases RONS generation in the myocardium, which appears to be the main cause of myocardial damage. RONS produced in excess in the myocardium cause cardiomyocyte injury, apoptosis, and cell necrosis (42). In this study, cardiac hypertrophy was observed after long-term exposure to IHH, as evidenced by the significant increase in the heart weight-to-body weight ratio.…”
Section: Discussionmentioning
confidence: 47%
“…Exposure to IHH increases RONS generation in the myocardium, which appears to be the main cause of myocardial damage. RONS produced in excess in the myocardium cause cardiomyocyte injury, apoptosis, and cell necrosis (42). In this study, cardiac hypertrophy was observed after long-term exposure to IHH, as evidenced by the significant increase in the heart weight-to-body weight ratio.…”
Section: Discussionmentioning
confidence: 47%
“…The examples below indicate that hypoxia may cause profound physiological changes; in humans, hypoxia is known inter alia from obstructive sleep apnoea. Chronic intermittent hypoxia may cause cardiovascular deterioration in animals and humans that may be due to oxidative stress, systemic inflammation, sympathetic activation, decrease of bone marrow-derived endothelial progenitor cell mobilization, which decreases repair of endothelial injuries, systemic and pulmonary arterial hypertension, and heart failure (Dumitrascu et al 2013; Wang et al 2013b; Yin et al 2012, 2014). In the lungs, hypoxia can induce oxidative stress and inflammation that can cause bronchial vasoconstriction, pulmonary oedema, vascular remodelling and pulmonary hypertension (Araneda and Tuesta 2012).…”
Section: Genotoxicitymentioning
confidence: 99%
“…34 The cardiovascular response to CIH depends on the severity, frequency and duration of IH exposure and generally progresses from adaptation to maladaptation. 5,[35][36][37] Moderate IH has been associated with a beneficial response at the cardiovascular level, 38 including a protective or ischaemic preconditioning effect, while severe CIH exacerbates injury. 35,39 Here, we studied a long-term severe pattern of IH simulating severe OSA.…”
Section: Discussionmentioning
confidence: 99%